Harnessing Youth and Policy Support for Sustainable Cultural Businesses in Nepal - Lamichhane, Basu Dev; Acharya, Krishna Raj; Lamichhane , Saujan; Pandey, Prerna (NPRC Journal of Multidisciplinary Research, 2025)
Nepal’s rich cultural heritage offers a unique pathway toward sustainable development, particularly through the promotion of green economy practices within cultural industries. However, there is limited understanding of how local entrepreneurs, especially Newar businesspersons in Kathmandu Valley, perceive the role of policies, youth involvement, and green practices in enhancing cultural businesses. This study aims to examine these perceptions and identify gender-based differences to inform policy formulation and strategic interventions. A quantitative research design was employed, collecting data from 386 randomly selected Newar entrepreneurs using a structured survey. Data were analyzed with SPSS through descriptive statistics, cross-tabulation, and Chi-square tests to explore associations between variables such as gender and attitudes toward green policies and youth engagement. Results revealed significant gender differences: female entrepreneurs demonstrated stronger support for policy incentives encouraging green practices and youth involvement, while male entrepreneurs showed skepticism about integrating green curricula and local cultural business support. The findings underscore the importance of gender-sensitive policies and targeted programs that promote sustainable and inclusive cultural entrepreneurship. Based on these insights, the study recommends that policymakers design tailored interventions that enhance women’s participation, foster youth engagement, and build awareness of the benefits of green practices in cultural industries. Strengthening institutional support and providing access to green finance are vital for scaling up sustainable cultural businesses, ultimately contributing to Nepal’s green growth and cultural preservation.